The role of influencers on consumer involvement, belief and purchase intent in the healthy food industry - Marinier, Chloé (2021)
This dissertation aims to understand the impact of influencers on involvement, belief and purchase intention in the healthy food industry. The research explores in detail the extent to which two main factors of influencer perceived credibility and their ability to engage the consumer, have an impact on the variables analyzed: involvement with healthy choices, positive beliefs about healthy choices and purchase intention related to healthy food choices. The study follows an experimental design with results analyzed between two groups of subjects: one exposed to an influencer post on the social network Instagram and another one who was not subjected to any post. The results analysis between the two groups reveals, first, that influencers have a statistically significant impact on the consumer's involvement, belief and purchase intention in healthy food choices. The analysis also confirms that the perceived credibility of the influencer and its ability to engage the consumer both have an impact on the consumer's involvement, belief and purchase intention in the healthy food industry.